2016
DOI: 10.1016/j.jceh.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HBc Screening of Blood Donors in Bangladesh: Relevance to Containment of HBV Propagation

Abstract: Objectives: To avoid further transmission of hepatitis B virus (HBV) infection, blood is tested for hepatitis B surface antigen (HBsAg) before transfusion. However, post-transfusion hepatitis B has been detected in clinics after transfusion of HBsAg-negative blood. The study presented here was undertaken to assess if HBsAg-negative blood is free from HBV or not. Methods: Sera were collected from 398 blood donors who were negative for HBsAg. Out of 398 blood samples, antibody to hepatitis B core antigen (ant-HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…A study has shown that HBV DNA is prevalent in HBsAgnegative blood. 405 Thus, the quality assurance of HBsAg testing kits and safety of HBsAg-negative blood, which has not been tested for anti-HBc or nucleic acids, needs Government attention. It might not be practical to test blood samples with nucleic-acid amplification as a preventive measure; however, testing for anti-HBc could be accommodated in Bangladesh to prevent HBV transmission through blood transfusion.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…A study has shown that HBV DNA is prevalent in HBsAgnegative blood. 405 Thus, the quality assurance of HBsAg testing kits and safety of HBsAg-negative blood, which has not been tested for anti-HBc or nucleic acids, needs Government attention. It might not be practical to test blood samples with nucleic-acid amplification as a preventive measure; however, testing for anti-HBc could be accommodated in Bangladesh to prevent HBV transmission through blood transfusion.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…OBI has been described in Bangladesh amongst blood donors and in individuals with cirrhosis, hepatocellular carcinoma (HCC) and in subjects with raised serum alanine aminotransferase (ALT) 26,27 . Transmission of OBI can occur through transfusion of blood products that are positive for HBV DNA 28,29 , and has also been reported from vertical and early-childhood exposure 30 .…”
Section: Government Of Bangladesh Formulated a 'National Strategic Plmentioning
confidence: 99%
“…However, the study population was chosen based on clinical symptoms ranging from elevated blood ALT levels to hepatocellular carcinoma. A more representative analysis was recently produced by Jahan et al, where Hepatitis B DNA was detected in 7 out of 398 healthy individuals (1.8%), with five of them having abnormally elevated blood ALT levels (>30 IU/L) [63].…”
Section: Occult Hepatitis B Infection and Implications For Blood Donomentioning
confidence: 99%